Mapping evidence of intervention strategies to improving men’s uptake to HIV testing services in sub-Saharan Africa: A systematic scoping review - Hlongwa, Mbuzeleni; Mashamba-Thompson, Tivani; Makhunga, Sizwe; Hlongwana, Khumbulani (BMC infectious diseases, 2019)
HIV testing serves as a critical gateway for linkage and retention to care services, particularly in sub-Saharan African countries with high burden of HIV infections. However, the current progress towards addressing the first cascade of the 90-90-90 programme is largely contributed by women. This study aimed to map evidence on the intervention strategies to improve HIV uptake among men in sub-Saharan Africa. We conducted a scoping review guided by Arksey and O'Malley's (2005) framework and Levac et al. (2010) recommendation for methodological enhancement for scoping review studies. We searched for eligible articles from electronic databases such as PubMed/MEDLINE; American Doctoral Dissertations via EBSCO host; Union Catalogue of Theses and Dissertations (UCTD); SA ePublications via SABINET Online; World Cat Dissertations; Theses via OCLC; and Google Scholar. We included studies from January 1990 to August 2018. We used the PRISMA extension for scoping reviews (PRISMA-ScR): checklist and explanation. The Mixed Method Appraisal Tool version 2018 was used to determine the methodological quality of the included studies. We further used NVivo version 11 to aid with content thematic analysis. This study revealed that teaching men about HIV; Community-Based HIV testing; Home-Based HIV testing; Antenatal Care HIV testing; HIV testing incentives and HIV Self-testing are important strategies to improving HIV testing among men in sub-Saharan Africa. The need for improving programmes aimed at giving more information to men about HIV that are specifically tailored for men, especially given their poor uptake of HIV testing services was also found. This study further revealed the need for implementing Universal Test and Treat among HIV positive men found through community-based testing strategies, while suggesting the importance of restructuring home-based HIV testing visits to address the gap posed by mobile populations. The community HIV testing, as well as, HIV self-testing strategies showed great potential to increase HIV uptake among men in sub-Saharan Africa. However, to address poor linkage to care, ART should be initiated soon after HIV diagnosis is concluded during community testing services. We also recommend more research aimed at addressing the quality of HIV self-testing kits, as well as, improving the monitoring systems of the distributed HIV self-testing kits.